Research on a coordinated control strategy of three-phase photovoltaic converters based on a buck–boost DC link - Chen, Zhiyong; Hao, Zhifang; An, Jiakun; Fan, Wenyi; Huang, Yuan; Liu, Qunying (Frontiers in Energy Research, 2024)
A coordinated control strategy with current hysteresis loop is proposed to address the issues of high inductance current ripple and low conversion efficiency in photovoltaic systems, which can achieve real-time duty cycle regulation and fast maximum power tracking. This method is different from the conventional Buck-Boost integrated mode that uses one switch in the Buck-Boost DC-DC(Direct Current) link. Instead, it uses two switches to separate the Buck mode and Boost mode for the coordinated control. Based on the conventional fixed duty cycle determination method, a real-time duty cycle determination method is proposed by introducing changes in inductance current. In order to reduce the voltage harmonics at the output terminal and improve power transferring efficiency, the incremental conductance method is improved, and a maximum power point search method based on the steepest gradient descent is proposed. The specific experiment verified the proposed current hysteresis coordinated control method, effectively suppressing output voltage harmonics and improving high-power transferring efficiency, and the ripple of inductor current was also suppressed. Index terms-Photovoltaic panel(PV), Coordinated control strategy, Current hysteresis loop control, Buck-Boost circuit， DC-DC link.